Variasi Putaran Spindel Mesin Bubut 1000A mempengaruhi Hasil Uji Tarik dan Waktu Pengelasan pada Las Gesek - Buntu Lobo, Osmar; Keledar, Taufik; Keliolan, Samlan; Difinubun, Irfan (CV. IRA PUBLISHING, 2024)
Welding joints can be achieved by utilizing the heat generated between two surfaces that rub against each other. When two objects are continuously rubbed together, heat energy is likely to be produced. The greater the energy on both surfaces, the stronger the bond that forms at the joint. This study aims to determine the tensile test results from various spindle rotation variations nd how long the friction welding process takes. The method used is experimental, with each variation consisting of three samples, followed by calculating the average. Three spindle speed variations were tested: 700 rpm, 1080 rpm, and 1600 rpm. The results of this study show that a spindle speed of 1600 rpm produces the highest maximum stress of 377.71 MPa, followed by 1080 rpm with a maximum stress of 324.89 MPa, and 700 rpm with an average maximum stress of 268.41 MPa. Spindle speed also affects welding time. The welding time required at 700 rpm is 341.33 seconds, while at 1080 rpm, it is 210.33 seconds. The fastest time is achieved at 1600 rpm, taking only 148.33 seconds. The faster the spindle rotation, the hotter the metal surface becomes, which increases the surface bonding strength. Similarly, spindle speed affects welding time, as higher spindle speeds result in shorter welding times.